Pengaruh Media Gamification dalam Jaringan terhadap Hasil Belajar dan Sikap Berpikir dalam Belajar - A. Halim; Ismul Huda; Muhammad Syukri; Elisa Kasli; Lia Musnidar (Postgraduate, University of Mataram, 2022)
The concept of physics material for some students is a difficult concept. In fact, students tend to like to work together and be critical in asking questions, but lacks in building ideas between each other for understanding the concepts of physics material. This affects learning outcomes, namely about 20% of students have not met the minimum completeness criteria for the overall Physics material. Based on the problems above, the purpose of this study is to determine the effect of network gamification media on student learning outcomes and to determine differences in students' thinking attitudes in learning after gamification-based media is applied in the network. Gamification is one that implements the game concept in a non-game context to create a fun learning process. Gamification has various designs, one of which is crossword and has a bulleted aspect. This study aims to determine the effect of gamification media in the network on student learning outcomes. The method used in this research is quasi-experimental with Non-Randomized Posttest-Only Control Group Design with random sampling technique. Data was collected through test and non-test data. The results of the study were tested with the Ancova test showing a significance value of 0.325 > 0.05 which indicates the application of gamification media has no effect on learning outcomes. This can happen because the learning process is short and students explore independently without monitoring by the teacher and this is something that is still new for students. Based on the results of the questionnaire analysis proves that students become the ideal SK means more argumentative and critical. This shows that there is a difference after being given gamification media treatment on thinking attitudes in learning.